ENDO-OLIGOPEPTIDASE-A, A PUTATIVE ENKEPHALIN-GENERATING ENZYME, IN THE VERTEBRATE RETINA - Ferro, E.; Hamassaki, D. E.; Camargo, ACM; Britto, LRG (Lippincott-raven Publ, 1991)
Endo-oligopeptidase A, EC 3.4.22.19, converts small enkephalin-containing peptides into the corresponding enkephalins in vitro. We investigated the presence of endooligopeptidase A in the retina and its possible colocalization with enkephalins in retinal neurons. The specific activity of endo-oligopeptidase A found in pigeon retinae (30.3 +/- 7.3 mU/mg, mean +/- standard deviation) was four times higher than in rabbit retinae (7.0 +/- 1.1 mU/mg). The enzyme activity was not modified by EDTA, but it was enhanced by dithiothreitol and inhibited by zinc and 5,5'-dithiobis(2-nitrobenzoic acid). Immunohistochemical experiments with a purified antiserum against rabbit endo-oligopeptidase A revealed labeled neurons in both the inner nuclear layer and the ganglion cell layer of pigeon and rabbit retinae. Double-labeling immunofluorescence experiments demonstrated that about 90% of neurons containing endo-oligopeptidase A-like immunoreactivity also contained [Leu5]-enkephalin-like immunoreactivity. These colocalization results may represent an important step toward the demonstration of the possible involvement of endo-oligopeptidase A in enkephalin generation in vivo.
Keywords: ENDO-OLIGOPEPTIDASE-A; ENDOPEPTIDASE 22.19; ENKEPHALINS; OPIOID PEPTIDES; RETINAL NEUROPEPTIDES